Cortical plasticity: is it time for a change? - Kind, P (Elsevier, 1999)
Classical studies of plasticity in the visual cortex have been interpreted in terms of heterosynaptic competition between inputs. But an alternative type of ‘homosynaptic’ plasticity can explain many recent observations and has recently received experimental support. Perhaps both types of plasticity are important.